Analisis Pengaruh Pembiayaan Syariah dan Profitabilitas Bank Umum Syariah di Indonesia - Putri Novita Sari, Tania (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to analyze the influence of sharia financing consisting of murabahah, mudharabah and musyarakah financing on the profitability of sharia commercial banks for the 2018-2022 period. This type of research is classified as correlational research with a quantitative approach. The sample was selected using a purposive sampling technique and 8 Islamic commercial banks were determined as the sample for this research. The data analysis method uses multiple regression tests with hypothesis testing tested using the t test and F test. The results of the research state that partially mudharabah and musyarakah financing have an effect on the profitability of Sharia Commercial Banks for the 2018-2022 period as measured by the Return on Assets (ROA) proxy. Meanwhile, murabahah financing has no influence on the profitability of Sharia Commercial Banks for the 2018-2022 period. Thus, it can be stated that when there is a change in the type of mudharabah and musyarakah financing, it will affect the rise and fall in profitability obtained by Sharia Commercial Banks.